Digital Repositories in Private Clouds - Lumpa, Mushashu Mwansa (Department of Computer Science, 2020)
This study explores the use of digital repositories in private cloud environments. Private cloud computing is a cloud computing deployment model where compute and storage infrastructure are hosted on-premise by institutions. Digital repositories are used to manage institutions’ generated content. The advancement in cloud computing, the promise of elasticity, and the on-demand resource provisioning features of cloud systems are attractive characteristics that institutions can leverage on in delivering digital content to their audiences. In this study, a cloud computing operating system is deployed, and a means to install, monitor, manage and customise a repository system is developed. The repository system used is DSpace. Eucalyptus cloud software was used to setup a private cloud environment. A prototype application was developed to manage the installation and customisation of DSpace in the cloud environment. The prototype also included a feature to monitor the status of the running DSpace instances. To evaluate the efficiency, installation and customisation of DSpace in the cloud environment, two types of evaluations were carried out – a performance evaluation and a usability study. The performance evaluation was used to ascertain how long it takes to ingest and view items in DSpace. The experiments were carried out with varying numbers of running virtual machine instances in the cloud. The usability study evaluated the ease of installing and customising DSpace with the developed tool, called Lilu. A total of 22 participants took part in the usability study that was carried out within the premises of the University of Cape Town’s Computer Science Department. The participants belonged to 3 groups – experts, intermediate and beginners – based on their technical skill levels. The results show that private cloud environments can run institutional repositories with negligible performance degradation as the number of virtual machine instances in the cloud are increased. From the usability study, the tool developed was positively perceived. Participants in the study were able to install and customise DSpace. Institutional repositories can efficiently be installed and used in private cloud environments. Building tools that enable users to create single-click installations of the repositories, and creating user friendly interfaces to customise repositories would potentially increase the adoption and utilisation of private cloud environments by institutions.